The Role of Peroxisome Proliferator-Activated Receptors in Colorectal Cancer - Joo-In Park; Jong-Young Kwak (PPAR Research)
Colorectal cancer is one of the most common cancers in the world. Dietary fat intake is a major risk factor for colorectal cancer. Some nuclear hormone receptors play an important role in regulating nutrient metabolism and energy homeostasis. Among these receptors, special attention has been focused on the role of peroxisome proliferator-activated receptors (PPARs) in colorectal cancer, because PPARs are involved in regulation of lipid and carbohydrate metabolism. PPARs are ligand-activated intracellular transcription factors. The PPAR subfamily consists of three subtypes encoded by distinct genes named PPARα, PPARβ/δ, and PPARγ. PPARγ is the most extensively studied subtype of PPARs. Even though many investigators have studied the expression and clinical implications of PPARs in colorectal cancer, there are still many controversies about the role of PPARs in colorectal cancer. In this paper, the recent progresses in understanding the role of PPARs in colorectal cancer are summarized.